Formulasi Sediaan Krim Ekstrak Daun Pepaya (Carica Papaya L) sebagai Krim Pelembab Kulit - Setyani, Elsa Dewi; Daskar, Annajim; Pratiwi, Mida; Wijayanto, Wisnu Probo (Ners Akademika, 2024)
Purpose: The purpose of this study was to analyze the effect of the remote preceptor model on clinical practice learning on improving lecturer performance. The research design used quasi-experimental (The pre-test-post-test control group design). Method: The subjects of the study were taken by purposive sampling, namely 67 lecturers from midwifery institutions. Data were analyzed using descriptive and inferential statistics, namely the Chi Square test, Wilcoxon test and Mann Whitney test, Logistic Regression test. Results: There was a difference in the assessment of lecturer performance in the treatment group after being given a remote preceptor model compared to the control group with a mean difference of 10.98 (p <0.05). The remote preceptor model in clinical practice learning improved lecturer performance 9 times better (OR 8.681 (IK95%; 2.884 - 26.129)). Limitations: If the data collected is not detailed or structured enough, there may be shortcomings in the analysis or interpretation of the results. Contribution: The increase in lecturers' work occurred because there was effectiveness in the lecturers' time and energy so that they were able to carry out other tasks in accordance with the Tri Dharma of Higher Education.